Reformasi dalam Manajemen Berbasis Sekolah (MBS) - Imam, Drs. (EDUKASI: Jurnal Pendidikan Islam, 2015)
Education reform in Indonesia initiated the decentralization of education. Decentralization of education is meant kewengan central government and provincial government allowed only limited autonomy organizing activities specified in government regulations. While the local government authority covering the planning, implementation, monitoring, control and evaluation. Form of education decentralization is local autonomy which gave birth to school-based management. There are some who carried out the order of SBM reforms such as planning and evaluation of programs and curriculum management. In an effort optimasilsi implementation of MBS is the first regulation kewenagan clear between central and local government, and education units. To-two Need for Reform MBS according to the characteristics of Indonesia All three Application MBS in total. All four should be the training of MBS to the organizers of education and socialization model of MBS to Stakeholders